2006
DOI: 10.1557/proc-0946-hh10-09
|View full text |Cite
|
Sign up to set email alerts
|

Time Resolved Magneto-Optical Imaging in High Frequency AC Currents of YBa2Cu3O7-&[delta]Thin Films

Abstract: We present a time-resolved magneto-optical (MO) imaging study of high-temperature superconductor (HTS) in high-frequency alternating current (AC) regime. The evolution of the magnetic flux density distribution in YBa 2 Cu 3 O 7-δ (YBCO) thin film samples is studied in small steps of the phase of the applied AC current. The flux distribution at 10 K exhibits instabilities including flux jumps and flux creep. A quantitative analysis of the data allows us to obtain the current density evolution. The current profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…The values of J c can vary from 60 to 193 A/cm-width along the tape length at alternating intervals. TRMO imaging studies on YBCO thin film samples showed a symmetric phase evolution of the magnetic flux [7,9]. Several pieces 10 mm long were cut along the tape transversal direction.…”
Section: Methodsmentioning
confidence: 99%
“…The values of J c can vary from 60 to 193 A/cm-width along the tape length at alternating intervals. TRMO imaging studies on YBCO thin film samples showed a symmetric phase evolution of the magnetic flux [7,9]. Several pieces 10 mm long were cut along the tape transversal direction.…”
Section: Methodsmentioning
confidence: 99%